1997
DOI: 10.1159/000217460
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Activation of the Haemostatic System - Influence of Prolonged Thromboprophylaxis in Patients Undergoing Total Hip Arthroplasty

Abstract: Tissue injury during hip surgery results in the activation of the haemostatic system. The aim of this study was to detect markers of haemostatic activity, i.e. prothrombin fragment 1 and 2 (Fl+2), thrombin-antithrombin (TAT) complexes, fibrin degradation products (FbDP), and soluble fibrin monomers (SF), preoperatively, and on days 1, 7 and 35 in plasma of patients undergoing total hip arthroplasty. The study was part of a mul-ticentre study in which the patients were randomized to receive a subcutanous inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…In agreement with other authors [23,24] we found significantly increased levels of F1j2 as marker for thrombin generation after hip arthroplasty. This activation should be reflected by elevated β-TG and F1j2 levels post-operatively.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other authors [23,24] we found significantly increased levels of F1j2 as marker for thrombin generation after hip arthroplasty. This activation should be reflected by elevated β-TG and F1j2 levels post-operatively.…”
Section: Discussionsupporting
confidence: 93%
“…This activation should be reflected by elevated β-TG and F1j2 levels post-operatively. In agreement with other authors [23,24] we found significantly increased levels of F1j2 as marker for thrombin generation after hip arthroplasty. Increases in F1j2 and β-TG on day 10 post-operatively could have been due to the fact that the treatment with lowmolecular-mass heparin was withdrawn on day 5.…”
Section: Discussionsupporting
confidence: 93%
“…Similar differences have been reported previously [3,29]. Reasonable mechanisms for late-occurring VTE have been related to prolonged activation of the coagulation system [35,36]. A prolonged reduction in venous outflow has also been described, persisting for 6 weeks after hip replacement [37,38] but normalizing during the first week after knee replacement [39], differences that possibly could be explained by the use of tourniquet and the associated venous stasis and more extensive soft-tissue damage in knee replacement surgery, leading to extensive local release of tissue factor [12].…”
Section: Discussionsupporting
confidence: 83%